1996
DOI: 10.1021/jp943066n
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved X-ray Absorption Spectroscopy of Photoreduced Base-off Cob(II)alamin Compared to the Co(II) Species in Clostridium thermoaceticum

Abstract: We have made significant improvements in pump-probe time-resolved X-ray absorption spectroscopy that enable us to structurally describe chemical intermediates with short lifetimes. We demonstrate that X-ray preedge data for a 1 mM compound can be acquired with a high signal-to-noise ratio by time-resolved discrimination of fluorescent signals from a 13-element germanium detector. With the utilization of this novel time-multiplexed laser photolysis system coupled to a flow cell, we characterized the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…Thus, there is no obvious change in geometry associated with the variation of Glu34 or Glu63 as compared to WT- Ec RcnR. 75, 76 However, the XANES spectra for WT, E34A-, E34C-, E63A- and E63C - Ec RcnR are non-overlapping, and thus indicative of some change in the Co(II) coordination sphere. These differences were addressed by EXAFS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is no obvious change in geometry associated with the variation of Glu34 or Glu63 as compared to WT- Ec RcnR. 75, 76 However, the XANES spectra for WT, E34A-, E34C-, E63A- and E63C - Ec RcnR are non-overlapping, and thus indicative of some change in the Co(II) coordination sphere. These differences were addressed by EXAFS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the Co oxidation state of pristine B12 was 3þ [25,26]. Scheuring et al used timeresolved X-ray absorption spectroscopy to study pristine B12-Co(III) and base-off B12-Co(II), and found that the E 0 of Co (II) was lower than that of Co(III) by approximately 4.0e6.0 eV [27]. The Co K-edge E 0 of py-B12-300 is lower than that of pristine B12 by about 2.9 eV, indicating that the Co oxidation state may be a mixture of 3þ and 2þ.…”
Section: Structure Analysismentioning
confidence: 99%
“…Scheuring et al examined various six-, five-and four-coordinated B12 species. They found that the six-coordinated B12 species has an octahedral structure with a central Co(III) and the four-coordinated B12 species has a square-planar Corrin -structure with a central Co(II) [27]. Okada et al identified four-, five-and six-coordinated Co(II)-or Co(III)-based nitrogen-containing compounds, and concluded that the best catalysts of the ORR are four-coordinated Co(II)-based nitrogen-containing compounds with a coplanar chelate structure [33].…”
Section: Structure Analysismentioning
confidence: 99%
“…Mit dem Auftauchen von Synchrotrons der dritten Generation mit extrem hohen Photonenflüssen pro Röntgen-puls wurden die Untersuchungen von Molekülen in angeregten Zuständen in fehlgeordneten Medien dann entscheidend verbessert. Frühe Studien mit älteren Synchrotrons gingen hauptsächlich von drei Ansätzen aus: 1) Zeitauflösung durch Sperren des Detektors oder Unterbrechen des Rönt-genpulses, [22][23][24][25][26][27][28][29][30] 2) Abfangen von Molekülen im angeregten Zustand in kryogenen Matrices und Untersuchung mit stationären Methoden [31][32][33][34][35] und 3) energiedispersive Rönt-genabsorptionsspektroskopie, bei der die Struktur des angeregten Zustands innerhalb der Auslesezeit des Detektors ermittelt wird. [36][37][38][39][40][41] Die Zeitauflösung bei diesen frühen Arbeiten lag nur im Mikrosekundenbereich, weshalb viele angeregte Zustände, besonders Singulettzustände mit kurzer Lebensdauer, nicht untersucht werden konnten.…”
Section: Warum Ist üBer Die Strukturen Von Molekülen In Angeregtenunclassified